Structural response of stiffened plates in similitude under a turbulent boundary layer excitation. (October 2020) - Franco, Francesco; Berry, Alain; Petrone, Giuseppe; De Rosa, Sergio; Ciappi, Elena; Robin, Olivier
Abstract: In structural dynamics, similitude laws usually deal with simple configurations as thin flat plates with point forces. Only recently, few papers have analyzed stiffened shells or stochastic pressure loads. This research activity extends the applicability of some similitude laws, developed for thin flat plates under a turbulent boundary layer load, to ribbed plates forced by the same wall pressure fluctuations. The work addresses the problem of designing a scaled experimental test-article and, successively, of re-modulating the measured data in order to get the structural response of an original (unscaled) configuration. Due to the complexity of the structural domain, the design of a scaled configuration leads to a distorted similitude. Then, a simple approach, to circumvent the distortion effects, is proposed.